1997
DOI: 10.1093/ps/76.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Blood system response of chickens to changes in environmental temperature

Abstract: Hemodynamic changes were studied in broiler chickens during exposure to constant temperatures (10 to 35 C) or diurnal temperature cycles (10:30 C and 15:35 C), and during acute heat or cold. Packed cell volume (PCV) was significantly high at low constant temperatures (10 and 15 C), whereas at high temperatures (30 and 35 C) plasma volume (PV) was significantly high. A linear relationship between hematocrit and heart weight was observed and indicates an adaptation of heart mass to changes in cardiac output and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
81
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 28 publications
13
81
0
2
Order By: Relevance
“…Compared with NT chickens, CT chicks had significantly higher hematocrit which is in agreement with previous findings (Yahav et al, 1997;Ipek and Sahan, 2006), and can be a sign of enhanced erythropoiesis in CT. Thermoneutral zone of chickens is too narrow and exposure to suboptimal temperatures increases their oxygen demand (Julian et al, 1989), which stimulates erythropoiesis (Luger et al, 2003) leading to elevated red blood cells number and hematocrit. In the current study, CT birds showed higher levels of T 3 (Table 5) which is an indication of raised metabolic rate and increased oxygen demand in these chickens.…”
Section: Hematocritsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with NT chickens, CT chicks had significantly higher hematocrit which is in agreement with previous findings (Yahav et al, 1997;Ipek and Sahan, 2006), and can be a sign of enhanced erythropoiesis in CT. Thermoneutral zone of chickens is too narrow and exposure to suboptimal temperatures increases their oxygen demand (Julian et al, 1989), which stimulates erythropoiesis (Luger et al, 2003) leading to elevated red blood cells number and hematocrit. In the current study, CT birds showed higher levels of T 3 (Table 5) which is an indication of raised metabolic rate and increased oxygen demand in these chickens.…”
Section: Hematocritsupporting
confidence: 91%
“…Pulmonary hypertension triggers series of events, which finally lead to the ascites syndrome (Julian, 2000 and2007). During cold stress several studies have reported important physiological changes, including classic hematological changes and increased right ventricle weight per total ventricle weight (RV : TV) ratio (Yahav et al, 1997;Luger et al, 2003;Ipek and Sahan, 2006), but there is only very little or no information on the other physiological responses such as blood chemical alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The response of cellular mechanisms to the long-term effect of thermal conditioning is complex and contradicting observations were reported in earlier studies. One school of thought suggesting the high Hsp expression is associated with better heat tolerance (Wang & Edens 1993, 1998) while the other is low level of expression (Yahav et al 1997). The present findings were in accordance with Yahav et al (1997) wherein thermal conditioning during early age induced thermotolerance by adaptation and subsequent low level of Hsp expression.…”
Section: Discussionmentioning
confidence: 99%
“…One school of thought suggesting the high Hsp expression is associated with better heat tolerance (Wang & Edens 1993, 1998) while the other is low level of expression (Yahav et al 1997). The present findings were in accordance with Yahav et al (1997) wherein thermal conditioning during early age induced thermotolerance by adaptation and subsequent low level of Hsp expression. The mechanism to combat heat stress in the present study involves reducing hyperthermia by protecting the body tissues from being exposed to stress, which might be partly due to the stability of tissues to hyperthermia due to earlier conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…environmental (e.g., high eggshell temperatures during incubation, altitude, low ambient temperatures, etc.) (Yahav et al, 1997), and management (e.g., ventilation, disease status) factors Sahan et al, 2006). Although the peak incidence of ascites occurs in the 5 th or 6 th week of the growing period, the etiology of the disease may be initiated much earlier, even during the embryonic stage (Coleman & Coleman, 1991).…”
Section: Introductionmentioning
confidence: 99%